If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -7x + 3 = -3 + 21 + -3x Reorder the terms: 17 + 3 + -7x = -3 + 21 + -3x Combine like terms: 17 + 3 = 20 20 + -7x = -3 + 21 + -3x Combine like terms: -3 + 21 = 18 20 + -7x = 18 + -3x Solving 20 + -7x = 18 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 20 + -7x + 3x = 18 + -3x + 3x Combine like terms: -7x + 3x = -4x 20 + -4x = 18 + -3x + 3x Combine like terms: -3x + 3x = 0 20 + -4x = 18 + 0 20 + -4x = 18 Add '-20' to each side of the equation. 20 + -20 + -4x = 18 + -20 Combine like terms: 20 + -20 = 0 0 + -4x = 18 + -20 -4x = 18 + -20 Combine like terms: 18 + -20 = -2 -4x = -2 Divide each side by '-4'. x = 0.5 Simplifying x = 0.5
| 11+1=1012 | | 2.5/4=x-3/16 | | 40=4x-3 | | y=2/3x^2 | | (1/2)x-3=(3/4)x+1 | | 81=-3(5+4m) | | 0.5x-3=0.75x+1 | | n+n+n=180 | | 7(x+1)=2 | | -6(r-8)=90 | | 5d-2(4a+5)=7a | | 10+9-11-p=2(2p+4)-3(2p-2) | | -(8y+5z-5)= | | 5=u+3 | | -18x^3-X^2+11x-15=0 | | 2(3w-1)-7=9w | | -(1+7x)16(-7-x)=36 | | 2y+7=4x | | 8+3.4=3.4+8 | | 7-(4y-6)=8-5y | | 342/9 | | 83=-3(5+4m) | | 2(x-1)+3(2x+5)=21 | | 6*x^4-13*x^3+12*x^2-13*x+6=0 | | m-2m-4m+5= | | -234=-3x-12 | | 5y=x+25 | | -8x-11=76 | | 3x+9-x=8+x-5 | | 5h-(3h-2)=12 | | -60.75=-12+6.5x | | 9=w-3 |